Looking in the mirror: Attitudes toward disability - Sunaira Tejpar; Alana Butler (Canadian Society for Studies in Education, 2023)
This paper serves as a foundational piece, aiming to investigate the potential of critical disability theory (CDT) and disability critical race theory (DisCrit) in shedding light on students' perceptions of their own exceptionalities and how this can impact their educational achievement in subjects like math, physical education, and English. While there is a substantial body of research focusing on CDT, teacher attitudes, and non-identified student attitudes towards disabilities, there is a lack of research exploring the connections between CDT, DisCrit, and students' attitudes towards their own exceptionalities. It is crucial to acknowledge how students perceive their own exceptionalities, as internalizing ableist prejudice and discrimination can lead to students viewing their exceptionalities as hindrances or barriers, which can detrimentally affect their academic development. However, by embracing the activist work of CDT and DisCrit scholars and shifting ableist perspectives towards a strengths-based approach that highlights individuals' resilience and fortitude. This shift in mindset has the potential to enhance students' overall academic success.